Benefits of “Best for Groin” Strategy Leading to a Transapical TAVI Dominance - Imnadze, Guram; Franz, Norbert; Hofmann, Steffen; Kowalski, Marek; Billion, Michael; Ferdosi, Abbas; Warnecke, Henning (The Thoracic and Cardiovascular Surgeon, 2015)
Background Transcatheter aortic valve implantation (TAVI) is a recognized therapeutic option for high-risk and inoperable patients with aortic valve stenosis. The choice of access route is a matter of debate. We are presenting our 5-year experience of transapical TAVI dominance.Patients This single-center study includes 575 patients. Two groups were compared: transapical (TA) and transfemoral (TF) with 454 and 121 patients, respectively. Individual access route decision was made by our heart team following a clinical and computed tomography (CT) data based nonbiased strategy. The same team performed all procedures. The mean logistic EuroSCORE was significantly higher in the TA group, however, without difference in STS score. The number of patients with coronary artery disease, previous cardiac surgery, and low left ventricular ejection fraction was higher in the TA group. There were no significant differences in age and presence of other comorbidities.Results Procedural success in both TA and TF groups was high (97.9% and 97.6%). No patient died during the procedure. Patient survival (30 days: TF, 97.5% vs. TA, 95.7%; 1 year: TF, 94.6% vs. TA, 81.8%; 2 years: TF, 84.7% vs. TA, 76.7%; 3 years: TF, 59.9% vs. TA, 67.8%) and a low TF vascular complication rate (1.6%) are encouraging compared with other registry data.Conclusion A “no competition” team approach strategy along with an experienced hybrid team leads to fewer vascular complications and better outcomes for both TA and TF TAVI patients.
Keywords: aortic valve and root; heart valve; transapical; percutaneous (TAVI); heart valve surgery